PENGARUH VIRAL MARKETING DAN E-WOM TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS PRODUK ARTHA LDT) - Komariah, Nurul Dwi; Rachman, Riza; Pristika N, Rafika Febri; Murtakiyah, Wardah; Kolida, Firda Ukfatul; haniza P, Dwi Maryamah; Suliyana, Putri Mita (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
This research aims to determine the influence of viral marketing and E-WOM on purchasing decisions (study on Artha ldt products). Purchasing decisions arise because of public trust in the product which comes from reviews or viral marketing and E-WOM. The data analysis method used is multiple linear regression analysis. This analysis is used to find out how much influence the independent variables (Viral Marketing and E-WOM) have on the dependent variable (Purchasing Decisions). Data analysis techniques include validity tests, reliability tests, and classical assumption tests. The type of primary data used in this research is quantitative data. Quantitative data was obtained from questionnaires distributed to Arthta consumers. The sample used was 55 respondents. Secondary data in this research was obtained from observation and literature study.